The philosophy of social science : an introduction - Hollis, Martin (Cambridge [England] ; New York : Cambridge University Press, 1994)
Written in Martin Hollis' characteristically clear and incisive prose, this textbook will appeal to philosophers and social scientists alike as an outstanding introduction to the subject.
TOC
Includes bibliographical references (p. 261-265) and index.
SR
Keywords: Social sciences -- Philosophy